Sustainable Cropping Systems - Coulter, Jeffrey A. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Global crop production must substantially increase to meet the needs of a rapidly growing population. This is constrained by the availability of nutrients, water, and land. There is also an urgent need to reduce the negative environmental impacts of crop production. Collectively, these issues represent one of the greatest challenges of the twenty-first century. Sustainable cropping systems based on ecological principles are the core of integrated approaches to solve this critical challenge. This special issue provides an international basis for revealing the underlying mechanisms of sustainable cropping systems to drive agronomic innovations. It includes review and original research articles that report novel scientific findings on improvement in cropping systems related to crop yields and their resistance to biotic and abiotic stressors, resource use efficiency, environmental impact, sustainability, and ecosystem services.